Comparison between classical polyarteritis nodosa and single organ vasculitis of medium-sized vessels: a retrospective study of 25 patients and review of the literature. Issue 1 (2nd January 2016) - Kint, N.; De Haes, P.; Blockmans, D.
Abstract : Background:: Polyarteritis nodosa (PAN) is a rare form of systemic vasculitis, characterized by necrotizing inflammation of medium-sized vessels. In clinical practice, the distinction is made between a limited, mostly cutaneous, form and a generalized form. The Chapel Hill Consensus Conference of 2012 on the classification of the vasculitides classifies PAN as a medium vessel vasculitis, whereas the limited forms fall under the heading 'single-organ vasculitis' (SOV), with subdivions such as 'cutaneous arteritis' (formerly called cutaneous PAN) and 'others'. In this last category, forms of PAN limited to a single organ (e.g. testicle, gall bladder or appendix) should be categorized. The relation between classical and limited forms of PAN remains enigmatic. Objective:: To compare demographics, clinical characteristics and prognosis between SOV and generalized PAN. Methods:: Clinical files of all patients with a diagnosis of classical or limited PAN made in the departments of general internal medicine and dermatology between 1983 and 2013 in a tertiary care university hospital were reviewed. Results:: The patients of the SOV group tend to be younger, with a female predominance, while we observed a male predominance in the generalized PAN group. Relapses were more common in SOV than in classical PAN. None of the patients initially diagnosed with cPAN/SOV progressed to generalized disease. Discussion:: Though SOV and classical PAN share a lot of similarities, they are probably different disease entities, based on their different demographical, clinical and prognostic characteristics. The 1990 ACR-criteria for classical PAN are too broad since they allow patients with limited disease to be classified as classic PAN.